Fortalecimiento del razonamiento lógico matemático del cuarto año de Educación General Básica para el desarrollo de destrezas con criterio de desempeño de la Escuela "Angel Veliz Mendoza" del cantón Vinces; provincia de Los Ríos 2011 - 2012 - Martínez Ruiz, Erika Pilar (2012)
The ideas of Charles PEIRCE on the critical thought can help us to rethink our approach of the development of the understanding.PEIRCE (1966) defined the critical thought or reasoning like a process in which the razonador does with total conscience, a judgment or establishes a conclusion on the truth of something.It affirms that each case of thought I criticize begins with the observation of which it surprises, unexpected, that seems an anomaly, which causes that the person stops, it thinks and it looks for, to find something that helps him to explain the strange event. The logical reasoning talks about to the understanding use to happen from proposals to others, starting off of or known or which we create to know the stranger or the less known. is distinguished between. Types of inference.All reasoning or discursivo process is denominated, in general, inference.The mediate inferences are complex discursivos processes ', in which the conclusion derives from a series of judgments. The deduction and the induction. - The inductive inferences are complex discursivos processes that formulate universal conclusions from particular judgments, following, consequently, the inverse way of the deduction, that goes of the general to the individual that is of the abstract thing to concrete it. The analogy. - The reasonings by analogy are mediate inferences that go of the individual to the individual and consist of the attribution of a same predicate to different subjects in which a similarity, correspondence or correlation have been verified. Criteria for the education of procedures. As a result of the saying until now and in the sociocultural perspective of education and the learning, themain criterion to consider is the one to focus the activity of education and learning like an interactive social process that provokes and stimulates cognitivos processes in students and professors. Strategies of the classroom for the reasoning: To plan and to control the learning process.To appreciate the intrinsic value of the knowledge.To develop positive attitudes towards the learning.To control the emotions.To direct the attention in global and selective form.To select the main ideas.To organize and to structure the information.To analyze and to synthesize the information. To accede to the previous knowledge.To elaborate the information by means of analogies, images, examples and questions.To make inferences.To surpass conventional visions.To judge the ideas critically.To establish the personal value of the knowledge.To explore the memory of independent or systematic way.To apply the learned thing to different tasks.To evaluate the learned knowledge.To evaluate the quality of the activated processes Learning. Acquisition by the practice of a lasting conduct. It is a process of permanent change in the person whom it gives like result in the experience. Theory of the significant learning. The theory of the significant learning of Ausubel opposes east type of learning to the memorístico learning.The memorístico learning does not allow to use the knowledge of novel or innovating form. Conditions to obtain significant learning. The significant knowledge becomes base of new knowledge, because they are transformed into prerequirements of the new learnings."When greater it is the degree of significatividad of the made learning, as much greater it will be his functionality, it will be able to be related to a ampler scope of new situations and contents" Forms to acquire the learning.The learning is acquired of two forms:a) Learning by reception, occurs when the information is provided to the student in its final form.b) Learning by discovery, when the student must discover the content;the teacher gives tracks him so that he arrives at the learning. Constructivism. Ample body of theories that they have in common the idea that the people, as much individual as collectively, "constructs" their ideas on their average physicist, social or cultural.From that conception "to construct" the thought the term arises that it protects to all Strategies of significant learning: Summaries.Previous organizers.Illustrations.Graphical organizers.Analogies. Signalings. Conceptual maps and networks.Textual organizers. The understanding. It is to be able to take the knowledge and to use it in different forms. The knowledge, the abilities and the understanding are the actions in the company of the education. The knowledge is information at the hand.And if the knowledge is information at the hand, the abilities are performances of routine at the hand. The types of reading understanding are:The literal understanding, Its function is the one to obtain a meaning. The inferencial understanding, also Denominated interpretativa